The Role of Emotional Intelligence on the Development of Critical Thinking: A Study of Department of Accounting Students, Universitas Negeri Malang, Indonesia - Sulastri; Miranti Puspaningtyas; Iva Khoiril Mala (Arkus, 2023)
The accounting learning process requires students to have critical thinking skills. Critical thinking is called the process of making judgments based on analysis, interpretation, evaluation, inference, explanation, and reflection. Many factors influence critical thinking, one of which is emotional intelligence. Another factor that can influence critical thinking is conflict management. This study aimed to determine the role of emotional intelligence and the ability to manage conflict from students that affect critical thinking skills in learning activities. This study was an analytic observational study and used primary data obtained from interviews with respondents. A total of 75 respondents were included in this study. Data analysis was performed with the help of SPSS using multiple linear regression. Emotional intelligence has a positive and significant effect on critical thinking. This means that the higher the emotional intelligence of students, the higher their ability to think critically. Conflict management has no effect on critical thinking. This shows that even though students have good conflict management skills, this cannot affect students' critical thinking.